Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2011-2013 - Ningsih, Rum Royen, Drs. Atwal Arifin, Ak.,M.Si (2016)
This study aims to determine the effect of Financial Ratios Return on Equity in Manufacturing Company listed on the Indonesia Stock Exchange (BEI) 2011-2013. The population in this study are the financial statements of companies listed on the Indonesian Stock Exchange (BEI) in 2011-2013 as many as 107 companies. The sampling technique used was purposive sampling method sampling technique to sample the necessary requirements Sources of data obtained from financial statements issued Indonesia Capital Market Directory (ICMD). The dependent variable in this study using Return Stocks and independent variables, the Current Ratio (CR), Total Assets Turnover (TAT), Debt To Equity (DER), and Return On Assets (ROA) analysis tool is used is multiple regression analysis, the coefficient determination (R2), and hypothesis testing by t test and F test The results showed that only individual variables, and the Current Ratio (CR) and Return On Assets (ROA) significantly affects Retun stock. While the variable Debt To Equity (DER) and Total Assets Turnover (TAT) has no significant effect on stock prices. Keywords: Stock Return (RS), the Current Ratio (CR), Total Assets Turnover (TAT), Debt To Equity (DER), and Return On Asset (ROA)